MODEL ROLE PLAYING DALAM PEMBELAJARAN SIKLUS AKUNTANSI PERUSAHAAN DAGANG - Santoso, Jarot Tri Tri Bowo (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
Accounting lesson is considered as a difficult lesson by most students in SMK/SMA. It is even sometimes worse with the less ability of accounting teachers to select learning methods thatcan attract students’ attention and thought. Therefore, it is necessary to find an alternative learning which can help students to involve in the real situation which is fun and memorable. The learning model which can fulfill the fun situation is the role playing. The steps to implement this model in the learning of accounting cycle for trade firm are to divide students in groups and to give each of them an opportunity to play a role. In practice, each student changers the role weekly based on the order. The model makesstuents easier to understand the basic accounting and leads the teachers evaluate the materials if the lack of conformity occurs during the learning.